Analysis of factors affecting the impurity rate of mechanically-harvested maize grain in China - Huang, Zhaofu; Xue, Jun; Ming, Bo; Wang, Keru; Xie, Ruizhi; Hou, Peng; Li, Shaokun (International Journal of Agricultural and Biological Engineering, 2020)
The grain impurity rate is an important index for assessing the quality of mechanical maize harvesting. Therefore, it is of great significance to clarify the current situation of maize impurity rate and study the factors that affect the impurity rate in order to promote the development of mechanical maize harvesting technology. From 2012 to 2019, a total of 2504 maize impurity rate measurements were obtained. The results showed that the average impurity rate at maize harvest was 1.18% in China, in which the Huang-Huai-Hai summer maize area was 1.68%, which was significantly higher than the 0.65% in the Northwest spring maize area and 0.77% in the North China spring maize area. There was a significant positive correlation between the impurity rate and the moisture content of the maize harvest. The average moisture content of maize at harvest in Huang-Huai-Hai summer maize area was the highest at 27.55%, which was the main reason for the high impurity rate in this area. When harvesting different varieties with the same moisture content, there were significant differences in the impurity rate between different varieties. The cob hardness of the variety may also affect the impurity rate of maize. Different harvesters and weather conditions during harvesting are also important factors affecting the impurity rate. Therefore, by breeding fast dehydrated varieties and harvesting maize in time, the impurity rate of maize during mechanical harvesting can be effectively reduced. Keywords: mechanically-harvested maize grain, impurity rate, factors, analysis DOI: 10.25165/j.ijabe.20201305.6038 Citation: Huang Z F, Xue J, Ming B, Wang K R, Xie R Z, Hou P, et al. Analysis of factors affecting the impurity rate of mechanically-harvested maize grain in China. Int J Agric & Biol Eng, 2020; 13(5): 17–22.